Port Development and Competition in East and Southern Africa : Prospects and Challenges - Humphreys, Martin; Stokenberga, Aiga; Herrera Dappe, Matias; Iimi, Atsushi; Hartmann, Olivier (World Bank, Washington, DC, 2019)
Port Development and Competition in East and Southern Africa analyzes the 15 main ports in East and Southern Africa (ESA) to assess whether their proposed capacity enhancements are justified by current and projected demand; whether the current port management approaches sufficiently address not only the maritime capacity needs but also other impediments to port efficiency; and what the expected hierarchy of ports in the region will be in the future. The analysis confirms the need to increase maritime capacity, as the overall container demand in the ports in scope is predicted to begin exceeding total current capacity by between 2025 and 2030, while gaps in terms of dry and liquid bulk handling are expected even sooner. However, in the case of many of the ports, the issue of landside access—the ports’ intermodal connectivity, the ease of international border crossing, and the port-city interface—is more important than the need to improve maritime access and capacity. The analysis finds that there is a need to improve the operating efficiency in all of the ESA ports, as they are currently less than half as productive as the most efficient ports in the matched data set of similar ports across the world, in terms of efficiency in container-handling operations. Similarly, there is a need to improve and formalize stakeholder engagement in many of the ports, to introduce modern management systems, and to strengthen the institutional framework to ensure the most efficient use of the infrastructure and to be able to attract private capital and specialist terminal operators. Finally, given the ports’ geographic location and proximity to main shipping routes, available draft, and the ongoing port-and-hinterland development, the book concludes that Durban and Djibouti are the most likely to emerge as the regional hubs in ESA’s future hub-and-spoke system.